2020
DOI: 10.21809/rilemtechlett.2019.93
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-based self-healing concrete: evaluation of full scale demonstrator projects

Abstract: Bacteria-based self-healing concrete is an innovative concrete that contains a self-healing agent that provides the material with enhanced autonomous crack-sealing performance. A specific type of this concrete, based on a healing agent composed of bacterial spores and lactate as carbon source, has been developed and applied by the Delft University of Technology for over ten years. Under laboratory conditions it was proven that, depending on the dosage of healing agent, self-healing of cracks up to 0.8 mm width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…The obtained results suggested that all tested bacteria are part of the most commonly used type of bacteria in the MICP [11,30,31]. In recent scientific literature, Bacillus and similar genus (e.g., Lysinibacillus) present a good choice of Grampositive bacteria for alkaline matrix during MICP application [32][33][34][35]. It can be observed that the average size of wild-type Bacillus strains is different from the referent strain.…”
Section: Discussionmentioning
confidence: 95%
“…The obtained results suggested that all tested bacteria are part of the most commonly used type of bacteria in the MICP [11,30,31]. In recent scientific literature, Bacillus and similar genus (e.g., Lysinibacillus) present a good choice of Grampositive bacteria for alkaline matrix during MICP application [32][33][34][35]. It can be observed that the average size of wild-type Bacillus strains is different from the referent strain.…”
Section: Discussionmentioning
confidence: 95%
“…Five months after casting, no signs of cracking were detected. In 2016 bacterial self-healing concrete was used in two projects (124): the construction of prefabricated parts of a wastewater purification tank and in two walls of a water reservoir. Monitoring in the following two years suggested that the repairs were effective.…”
Section: Large Scale Testsmentioning
confidence: 99%
“…Improving self-healing is still in a lower TRL level, currently validated in relevant environments (16)(17)(18). • Bacteria concept has been validated in laboratory and field pilots (123,124), but the products are not generally produced at large scales (96,97). Currently, bacteria production is limited, which complicates its application in concrete structures, but its production may improve in the next years.…”
Section: Maturity Level Of the Technologymentioning
confidence: 99%
“…Although most of these studies were laboratorybased, a few conducted in the last five years were still related to the application of bio-cultures as healers and strength increasers in practical structural elements. Mors and Jonkers (2019), conducted several practical implementations on bio-engineered mortar and concrete. This was the largest practical study that mainly focused on the ability of bio-cultures, towards crack healing within a realistic environment.…”
Section: Jonkers (2011)mentioning
confidence: 99%
“…Figure 8. Application of bacteria-based self-healing repair mortar on actively leaking cracked concrete basement walls (Mors & Jonkers, 2019).…”
Section: Self-healing Mortarmentioning
confidence: 99%